Nursing workload in burn intensive care unit - Luciana Mendes Amadeu; Magda Cristina Queiroz Dell'Acqua; Meire Cristina Noveli Castro; Valéria de Castilho Palhares; Clarita Terra Rodrigues Serafim; Armando dos Santos Trettene
ABSTRACT Objectives: To measure the nursing workload in the Burn Intensive Care Units and evaluate its association with clinical variables, length of stay, and outcome of hospitalization. Methods: Cross-sectional study carried out in a Brazilian public large hospital. The study included 33 patients. The nursing workload was assessed using the Nursing Activities Score (NAS) every 24 hours. We performed 447 Nursing Activities Score assessments. For the statistical analysis, Student's t-test, ANOVA, and Spearman's correlation test were used. The considered significant difference was 5% (p ≤ 0.05). Results: The Nursing Activities Score mean was 84% (± 4.4), which corresponded to 20.2 hours. There was an association between the nursing workload and the patient's severity (p <0.010), burned body surface (p = 0.010), and hospitalization outcome (p = 0.020). Conclusion: Burn victims, assisted in the ICU, demanded a high nursing workload, which was influenced by clinical aspects and the hospitalization outcome. These findings point to the need to reconsider the nurse staffing related to this care profile.